ANALISIS PENGARUH VARIASI PENDINGIN MINYAK NYAMPLUNG DAN OLI TERHADAP PARAMETER KEAUSAN PAHAT HIGH SPEED STEEL (HSS) PADA PROSES BUBUT PIN SAMBUNGAN GERBONG KERETA - Prasetio, Dwi Angga Tary; Hermawan, Yuni; Dwilaksana, Dedi; Sidartawan, Robertus; Syuhri, Ahmad (STATOR: Jurnal Ilmiah Teknik Mesin, 2024)
The use of coolant in the machining process aims to reduce the temperature in the cutting area and reduce friction due to friction between the workpiece and the tool which has an impact on the surface quality of the product. Commercial coolants such as Dromus oil use minerals, which are non-renewable and have a negative impact on the environment. Therefore, to overcome this problem, several studies have been carried out to replace or combine commercial coolants with vegetable oils. In this research, an experiment was carried out on the effect of using nyamplung oil ascutting fluidby mixing three different liquids (nyamplung oil, dromus oil, and water) (25%:25%:50%, 20%:30%:50%, and 30%:20%:50%) and the influence of the contribution of Turning machining parameters on tool wear. Machining was carried out on S45C steel using HSS type M2 chisels. This research method uses the Taguchi methodorthogonal array L9(33) with 3 factors (spindle rotation speed, coolant variation, and cutting depth). The results of this experiment show that a coolant composition of 25%:25%:50% (nyamplung oil:dromus oil:water) in 100ml of liquid contributes to reducing tool wear. Based on the average value, it shows that the highest parameter contribution is spindle speed at 60.26%, followed by cutting depth with 29.14% and coolant variation with a contribution of 9.40%.